Impacts of land abandonment and climate variability on runoff generation and sediment transport in the Pisuerga headwaters (Cantabrian Mountains, Spain). Issue 3 (3rd July 2019) - Pisabarro, Alfonso; Pellitero, Ramón; Serrano, Enrique; Lopez-Moreno, Juan Ignacio
ABSTRACT: The Atlantic mountains of Spain are suffering a strong landscape change due to a widespread and intensive emigration to urban areas since the 1950s. This process, representative of global developments in an imminent future, is dominated by urban societies and leads to deep landscape changes in which crop fields and grasslands are abandoned and progressively covered by forest and shrubs. These dynamics have caused in turn a decrease in the runoff and a general slowdown of geomorphological processes. The impacts of land cover change have been simultaneous to an irregularity in precipitation and a significant increase of temperatures. With this background, this paper assesses in detail the impact of landscape change occurred over the last decades (twentieth and twenty-first centuries) on the water and sediment yield in the Pisuerga catchment headwaters (Cantabrian Mountains, N Spain). We analyzed the different components of Global Change in a catchment of 233 km 2 extent, that has passed from 15 to 2 habitants/km 2, from multiple data sources. Evolution of land cover was reconstructed from aerial photographs, remote sensing and other resources. The climatic parameters have been studied through meteorological stations, and the hydrological and sedimentological responses over time are based on available runoff data and sedimentological analysis. Our results show a significant decrease in water and sediment transport mainly driven by vegetation increase occurred in a non-linear way, more intense immediately after abandonment. This fact opens the opportunity to control more accurately water resources in Mediterranean catchments through land use management.